2010
DOI: 10.1371/journal.pgen.1000888
|View full text |Cite
|
Sign up to set email alerts
|

Trait-Associated SNPs Are More Likely to Be eQTLs: Annotation to Enhance Discovery from GWAS

Abstract: Although genome-wide association studies (GWAS) of complex traits have yielded more reproducible associations than had been discovered using any other approach, the loci characterized to date do not account for much of the heritability to such traits and, in general, have not led to improved understanding of the biology underlying complex phenotypes. Using a web site we developed to serve results of expression quantitative trait locus (eQTL) studies in lymphoblastoid cell lines from HapMap samples (http://www.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
1,098
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,222 publications
(1,158 citation statements)
references
References 30 publications
56
1,098
2
2
Order By: Relevance
“…In total, we determined that 23,951 out of 39,165 (61%) statistically significant GWAS SNPs are eQTLs, which is consistent with previous findings that GWAS SNPs are enriched for eQTLs (p < 0.0001 for 10,000 random sets of 39,165 SNPs at MAF > 0.01 and r 2 > 0.3; average eQTL number ¼ 9,022). 13,31 Reproducibility and Mediation Effects of trans-eQTLs In accordance with previous results, 32 12 as a reference database, we found that 331 out of 1,686 (20%) transeQTL-trans-eGene pairs from the database were statistically significant (at p < 1 3 10 À7 ) in our results. Among them, 323 pairs (98%) have concordant directions of effects (Table S4).…”
Section: Results Eqtls Associated With Complex Disease Traitssupporting
confidence: 92%
“…In total, we determined that 23,951 out of 39,165 (61%) statistically significant GWAS SNPs are eQTLs, which is consistent with previous findings that GWAS SNPs are enriched for eQTLs (p < 0.0001 for 10,000 random sets of 39,165 SNPs at MAF > 0.01 and r 2 > 0.3; average eQTL number ¼ 9,022). 13,31 Reproducibility and Mediation Effects of trans-eQTLs In accordance with previous results, 32 12 as a reference database, we found that 331 out of 1,686 (20%) transeQTL-trans-eGene pairs from the database were statistically significant (at p < 1 3 10 À7 ) in our results. Among them, 323 pairs (98%) have concordant directions of effects (Table S4).…”
Section: Results Eqtls Associated With Complex Disease Traitssupporting
confidence: 92%
“…As GWAS hits are often expression quantitative trait loci (eQTLs) [Nicolae DL et al, 2010], we asked whether this is also true for the above variants. The correlation between genotype and the expression levels of the respective gene transcripts was examined in the temporal lobe (N = 162), the prefrontal cortex (N = 88), as well as in the combined sample (N = 250), adjusting for brain region.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, GWASascertained phenotype-associated single-nucleotide polymorphisms (SNPs) are enriched in cis-eQTLs. 15 It is recognized that cis-eQTLs are highly tissue-specific. 16,17 However, the acquisition of the appropriate tissue type is logistically challenging and the majority of eQTL studies were based on lymphoblastoid cell lines (LCLs).…”
Section: Introductionmentioning
confidence: 99%